1997
DOI: 10.1016/s1090-3801(97)90103-8
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of codeine‐6‐glucuronide after intravenous administration

Abstract: Centrally administered codeine glucuronide has been shown to exhibit antinociceptive properties with decreased immunosuppressive effects compared to codeine. In this study, codeine-6-glucuronide was administered to rats, and its analgesic effect was compared to that of codeine. The concentrations of codeine and its metabolites in plasma and brain were also determined at the peak response time after administration of each compound. Receptor-binding studies with rat brain homogenates and affinity profiles were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 25 publications
(10 reference statements)
0
40
0
Order By: Relevance
“…Codeine is a weak opioid that is metabolized in the liver to morphine and the main effect of codeine is thought to be mediated via -receptors, mainly through the main metabolites, morphine and morphine-6 glucoronide (Guay et al, 1987;Srinivasan et al, 1997). Seven percent of white people lack the ability to metabolize codeine, whereas 25% of Ethiopians are ultrarapid metabolizers because of a polymorphism of the enzyme responsible for this metabolism (P4502D6) (Poulsen et FIG.…”
Section: B Opioids With Weak Affinity For the -Opioid Receptormentioning
confidence: 99%
“…Codeine is a weak opioid that is metabolized in the liver to morphine and the main effect of codeine is thought to be mediated via -receptors, mainly through the main metabolites, morphine and morphine-6 glucoronide (Guay et al, 1987;Srinivasan et al, 1997). Seven percent of white people lack the ability to metabolize codeine, whereas 25% of Ethiopians are ultrarapid metabolizers because of a polymorphism of the enzyme responsible for this metabolism (P4502D6) (Poulsen et FIG.…”
Section: B Opioids With Weak Affinity For the -Opioid Receptormentioning
confidence: 99%
“…A similar observation was made by Gerostamoulos et al in a summary of toxicological findings in 6 drugrelated deaths with codeine as the principal toxicological agent [24], where morphine was reported in 2 of 6 cases. Some studies have suggested morphine-independent central nervous effects of codeine, presumably mediated through codeine itself or its CYP2D6-independent metabolites C6G and norcodeine [29][30][31], but direct evidence for such a mechanism is still lacking. Receptor affinity studies have demonstrated a 100-600-fold greater opioid m-receptor affinity for morphine and M6G than for codeine, C6G and norcodeine [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…51.23). Codeine has a low affinity for opioid receptors and the analgesic effect is due to its conversion to morphine, although the relative contributions of morphine and the metabolite codeine-6-glucuronide to analgesia are discussed (Srinivasan et al 1997). Its antitussive actions probably involve distinct receptors that bind codeine itself.…”
Section: Codeinementioning
confidence: 99%